Types and properties of wood adhesives / Nur Hayati Hashim @ Ho Pok Seng - Hashim @ Do Pok Seng, Nur Hayati (2004)
Literature search was carried on the types and properties of adhesives used in wood industry. Adhesives are classified into two broad categories s namely natural adhesives and synthetic adhesives. Typical natural adhesives are either carbohydrate or protein based. They are mainly derived from animal and vegetables sources or from inorganic material, while, synthetic adhesives are man-made polymers, which resemble natural adhesives in physical characteristic but be tailored to meet specific woodworking requirements. Synthetic adhesives are created to fulfill the need for better performing adhesives in industrial revolution. Every adhesives, either natural adhesives or synthetic adhesives have their own properties and characteristic which suitable with its uses.